Religions of the Silk Road - Foltz, R. author. aut Link
XIII, 190 p. 2 illus.
Keywords: Drawing on the latest research and scholarship, this newly revised and updated edition of Religions of the Silk Road explores the majestically fabled cities and exotic peoples that make up the romantic notions of the colonial era.